The nixie's song - DiTerlizzi, Tony.; Black, Holly (New York : Simon and Schuster Books for Young Readers, 2007)
Eleven-year-old Nick, his stepsister Laurie, and his big brother, Julian (plus a familiar face from the original Spiderwick Chronicles) try to figure out the best way to stop a host of rampaging giants before all of Florida goes up in smoke.
Keywords: Brothers and sisters -- Juvenile fiction; Fairies -- Juvenile fiction; Giants -- Juvenile fiction; Magic -- Juvenile fiction; Florida -- Juvenile fiction; Fantasy fiction